Greywater Treatment with Oxidative Agents - Ungvári, Csaba; Izbékiné Szabolcsik, Andrea; Ildikó (International Journal of Engineering and Management Sciences, 2018)
In our research we pretreated synthetically produced greywaters with filtration on various filters, then we treated the samples with oxidative agents. We characterised the quality of greywater samples with several parameters. We investigated these parameters on the untreated, pretreated, and oxidated samples as well. We evaluated the efficiency of the treatments by measuring the characteristic parameters. In addition, we investigated the changes on the filter media’ surface with a scanning electron microscope (SEM). It was shown, that the most effective treatment combination for the greywater’s preparation for reuse is the filtration on silica sand or activated charcoal and silica sand combined filter media, then oxidation with hydrogen peroxide (10 mmol/dm3).